Lanthanide sorbent based on magnetite nanoparticles functionalized with organophosphorus extractants. Issue 3 (25th June 2015) - Basualto, Carlos; Gaete, José; Molina, Lorena; Valenzuela, Fernando; Yañez, Claudia; Marco, Jose F
Abstract: In this work, an adsorbent was prepared based on the attachment of organophosphorus acid extractants, namely, D2EHPA, CYANEX 272, and CYANEX 301, to the surface of superparamagnetic magnetite (Fe3 O4 ) nanoparticles. The synthesized nanoparticles were coated with oleic acid, first by a chemisorption mechanism and later by the respective extractant via physical adsorption. The obtained core–shell functionalized magnetite nanoparticle composites were characterized by dynamic light scattering, scanning electron microscopy, transmission electron microscopy, thermogravimetry, infrared absorption and vibrating sample magnetometry. All the prepared nanoparticles exhibited a high saturation magnetization capacity that varied between 72 and 46 emu g −1 and decreased as the magnetite nanoparticle was coated with oleic acid and functionalized. The scope of this study also included adsorption tests for lanthanum, cerium, praseodymium, and neodymium and the corresponding analysis of their results. Sorption tests indicated that the functionalized nanoparticles were able to extract the four studied lanthanide metal ions, although the best extraction performance was observed when the sorbent was functionalized with CYANEX 272, which resulted in a loading capacity of approximately 12–14 mgLa /gMNP . The magnetization of the synthesized nanoparticles was verified during the separation of the lanthanide-loaded sorbent from the raffinate by using a conventional magnet.